2021
DOI: 10.1096/fj.202101064rr
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and chemical cues synergistically promote human venous smooth muscle cell osteogenesis through integrin β1‐ERK1/2 signaling: A cell model of hemodialysis fistula calcification

Abstract: Arteriovenous fistula (AVF) is the vascular access of choice for renal replacement therapy. However, AVF is susceptible to calcification with a high prevalence of 40%–65% in chronic hemodialysis patients. Repeated needle puncture for hemodialysis cannulation results in intimal denudation of AVF. We hypothesized that exposure to blood shear stress in the medial layer promotes venous smooth muscle cell (SMC) osteogenesis. While previous studies of shear stress focused on arterial‐type SMCs, SMCs isolated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…As the AVF intima is shed due to repeated cannulation, the media is directly exposed to the fluid shear force of the blood and is more susceptible to chemical signals (phosphate molecules), which may contribute to the venous osteogenesis. Yang et al [ 115 ] established a venous cell model of AVF using a fluid shear device combined with high phosphorus medium to simulate a uremic environment. The results showed that hydrodynamic stimulation had an additive effect on the upregulation of the osteogenic marker Runx2 in VSMCs at an early stage under shear stress and high phosphorus environment.…”
Section: Molecular Mechanisms Of Mechanical Stress-mediated Vascular ...mentioning
confidence: 99%
“…As the AVF intima is shed due to repeated cannulation, the media is directly exposed to the fluid shear force of the blood and is more susceptible to chemical signals (phosphate molecules), which may contribute to the venous osteogenesis. Yang et al [ 115 ] established a venous cell model of AVF using a fluid shear device combined with high phosphorus medium to simulate a uremic environment. The results showed that hydrodynamic stimulation had an additive effect on the upregulation of the osteogenic marker Runx2 in VSMCs at an early stage under shear stress and high phosphorus environment.…”
Section: Molecular Mechanisms Of Mechanical Stress-mediated Vascular ...mentioning
confidence: 99%